Validating muscle mass cutoffs of four international sarcopenia‐working groups in Japanese people using DXA and BIA - Yosuke Yamada; Minoru Yamada; Tsukasa Yoshida; Motohiko Miyachi; Hidenori Arai (Wiley, 2021)
Abstract Background The Asian Working Group for Sarcopenia (AWGS) 2019 recommended the use of dual‐energy X‐ray absorptiometry (DXA) or bioelectrical impedance analysis (BIA) to assess appendicular lean mass (ALM). AWGS, European Working Group on Sarcopenia in Older People 2 (EWGSOP2), Foundation for the National Institutes of Health Sarcopenia Project (FNIH), and International Working Group on Sarcopenia (IWGS) reported different cutoff values for sarcopenia. We aimed to validate these cutoff values in a Japanese population using DXA and two different devices of segmental multi‐frequency BIA (MF‐BIA). Methods We examined the data of Japanese individuals aged 18-86 years using the DXA (n = 756) and two 8‐electrode MF‐BIA devices (InBody and TANITA MC) (n = 1884). To validate these cutoff values, we used a population aged 18-40 years, and calculated the 95% confidence intervals (CIs) of [mean−2SD]. Results In DXA, the 95%CIs of [mean−2SD] for ALM/Ht2 were 5.2-5.8 and 6.6-7.3 kg/m2 in women and men, respectively. The AWGS (<5.4 in women and <7.0 in men), and IWGS (≤5.67 in women and ≤7.23 in men) cutoffs were acceptable. Regarding TANITA MC, the 95%CIs of [mean−2SD] for ALM/Ht2 were 5.6-6.0 and 6.9-7.4 kg/m2 in women and men, respectively. The AWGS (<5.7 in women and <7.0 in men), EWGSOP2 (<6.0 in women and <7.0 in men), and IWGS cutoffs were acceptable. Regarding InBody, the 95%CIs of [mean−2SD] for ALM/Ht2 were 4.8-5.2 and 6.4-6.8 kg/m2 in young women and men, respectively. All cutoff values were too high compared to those measured by InBody. InBody and TANITA MC were highly correlated (P < 0.001), but the values by InBody were significantly lower than those by TANITA MC or DXA. Using Yamada's equation for InBody raw data, the AWGS, EWGSOP2, or IWGS cutoffs were acceptable. The BMI‐adjusted muscle mass cutoff values were <0.60 and <0.82 m2 in women and men, respectively. We also obtained the 20th percentile in older adult population (ALM/Ht2, <6.2 in women and <7.5 in men for TANITA MC; <5.4 in women and <7.0 in men for InBody). Conclusions The AWGS and IWGS cutoffs were valid for DXA, and the AWGS, IWGS, and EWGSOP2 cutoffs were valid for TANITA MC in Japanese population. Because the prevalence of sarcopenia is too low particularly in women when using those criteria, the 20th percentile might be a good alternative criteria. If the ALM original InBody values are used, the cutoffs should be <5.0 kg/m2 in women and <6.6 kg/m2 in men.